2018
DOI: 10.1177/0267659117747046
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrafiltration on end-cardiopulmonary bypass hematocrit during cardiac surgery

Abstract: The use of UF during CPB resulted in significant increases in end-hematocrit, with the greatest benefit shown when volumes were under 2.5 L. We saw a positive linear benefit up to 2.5 L removed and, thereafter, in most procedures, the benefit leveled off. However, of note is markedly decreased urine output on bypass as the ultrafiltration volumes increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
(13 reference statements)
0
15
0
2
Order By: Relevance
“…The field of medicine is the lowest observed area of research found in this review. However, medicine has a higher research input in other membrane-based processes such as ultrafiltration where the membrane pore diameter is more appropriate for effective removal of certain contaminants [24] and hemoconcentration during cardiopulmonary bypasses [25].…”
Section: General Research Trends Since 2009mentioning
confidence: 99%
“…The field of medicine is the lowest observed area of research found in this review. However, medicine has a higher research input in other membrane-based processes such as ultrafiltration where the membrane pore diameter is more appropriate for effective removal of certain contaminants [24] and hemoconcentration during cardiopulmonary bypasses [25].…”
Section: General Research Trends Since 2009mentioning
confidence: 99%
“…We have previously shown that the use of ULF during CPB does increase end-Hct levels with the greatest benefit seen when ULV volumes were under 2,500 mL. 23 More recently, however, we have questioned the use of ULF as a means of reducing RBC transfusion even after 1,300 mL of plasma water removed. 24 Most of the studies that have demonstrated an effect of ULF on RBC transfusion have combined ULF with other blood management techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery remains one of the greatest consumers of blood products. Despite the studies those report the benefit of ultrafiltration, it is used less frequently in adult cardiac surgery [34]. Boodhwani et al reported significant decrease in surgical blood loss by using ultrafiltration in the metaanalysis of 11 articles.…”
Section: Discussionmentioning
confidence: 99%